Development of the ice resistance series chart for icebreaking ships - Chun-Ju Lee; Tae-Hwan Joung; Jae-Moon Lew (International Journal of Naval Architecture and Ocean Engineering, 2018)
The ice resistance series charts for icebreaking ships were developed through a series of systematic model tests in the ice tank of the Korean Research Institute of Ship and Ocean Engineering (KRISO). Spencer's (1992) component-based scaling system for ship-ice model tests was applied to extend the model ship correlations. Beam to draft ratio (B/T), length to beam ratio (L/B), block coefficient (CB) and stem angle (α) were selected as geometric parameters for hull form development. The basic hull form (S1) of twin pod type with B/T of 3.0, L/B of 6.0, CB of 0.75 and stem angle of 25° was generated with a modern hull design concept. A total of 13 hulls were designed varying the geometric parameters; B/T of 2.5 and 3.5, L/B of 5.0 and 7.0, CB from 0.65 to 0.85 in intervals of 0.05, and 5 stem angles from 15° to 35°. Ice resistance tests were first carried out with the basic hull form in level ice with suitable speed. Four more tests for CB variations from 0.65 to 0.85 were conducted and two more for beam to draft and length to beam ratios were also performed to study the effect of the geometric parameters on ice resistance. Ice resistance tests were summarized using the volumetric coefficient, CV (=∇/L3), instead of L/B and CB variations. Additional model tests were also carried out to account for the effect of the stem angle, ice thickness and ice strength on ice resistance. In order to develop the ice resistance series charts with a minimum number of experiments, the trends of the ice resistance obtained from the experiments were assumed to be similar for other model ship with different geometric parameters. A total of 18 sheets composed of combinations of three different beam to draft ratios and six block coefficients were developed as a parameter of CV in the low speed regions. Three correction charts were also developed for stem angles, ice thickness and ice strength respectively. The charts were applied to estimate ice resistance for existing icebreaking ships including ARAON, and the results were satisfactory with reasonable accuracy. Keywords: Ice resistance series chart, Icebreaking ship, Ice thickness and strength, Stem angle, Correction chart